Inversion hierarchical manner effect on the development of distinctive force as quickly as Accuracy and performance of the pressing in tennis with young players - Mahdi, Nawal; Abduh Reda, Inaam (Journal of Physical Education, 2015)
The skill pressing in tennis of the difficult skills on the players being the need to high physical qualities enable them to carry out this skill, and after reviewing the scientific sources found that there are several methods can have a qualitative and effective influence in the development of muscle strength characteristic speed with which overwhelm the skill that appear in player movement, due to the lack of research in this area and private tennis felt the researcher to use style hierarchy Almtaaks and find out the extent of its influence in the development of distinctive force as soon as the skill pressing a contribution to accuracy in the use of a few to use methods to develop that ability and skill, and that the results that will be accessed give us the amount of the evolution in muscle strength characteristic speed and skill pressing accuracy tennis subject of research, and the aim of the research, to identify the impact of style hierarchy Almtaaks to develop distinctive power speed and accuracy performance skill pressing for young players in tennis, and assumed researcher There are no significant differences between tribal tests and a posteriori in force characteristic speed and accuracy performance skill pressing for young players in tennis, opting researcher experimental design per set, and represents the community Find my players Baghdad clubs in tennis’s (13) player was research sample them choose the way intentional’s (8) players, was chosen for the players (2) for the purpose of conducting reconnaissance experience and (6) for the players to experience the major search by (46.154%) of the original community, and statistical Aalosail, percentage, mean, standard deviation, median, convolution coefficient, test (T-test) of the samples correlated, and concluded the style hierarchy Almtaaks a positive influence in the development of distinctive force as soon as the arms and legs and pressing the accuracy of the young tennis players, and recommended the adoption of the training curriculum training Almtaaks hierarchical method when some physical training and skills development for young famous tennis stage setup